Pemetaan Objek Wisata Kabupaten Penajam Paser Utara Berbasis Sistem Informasi Geografis - Hamrin, Hamrin; Agustin, Adinda Serly Eska; Anggraini, Olivia Monika; Sali, Armilia Prestia (Journal of Geographical Sciences and Education, 2026)
Penajam Paser Utara (PPU) Regency has a strategic position due to its proximity to the Nusantara Capital City and is supported by diverse natural and cultural tourism potential. However, the development of the tourism sector in this region is still constrained by the limited availability of systematically and spatially integrated data and information on tourism site locations. This study aims to map the spatial distribution of tourism objects in PPU Regency using a Geographic Information System (GIS). This research employs a qualitative descriptive method with descriptive and spatial analysis. The results indicate that there are 18 tourism sites consisting of 9 natural attractions, 8 artificial attractions, and 1 cultural attraction, distributed across four districts: Penajam, Babulu, Waru, and Sepaku. GIS-based mapping is able to present the spatial distribution of tourism objects in a visual, informative, and easily accessible manner, thereby supporting tourists, local communities, and regional governments in tourism planning and development.